2020
DOI: 10.5999/aps.2019.00283
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors that affect drainage volume after expander-based breast reconstruction

Abstract: Background Closed-suction drains are widely used in expander-based breast reconstruction. These drains are typically removed using a volume-based criterion. The drainage volume affects the hospital stay length and the recovery time. However, few studies have analyzed the factors that influence drainage volume after expander-based breast reconstruction. Methods We retrospectively analyzed data regarding daily drainage from patients who underwent expander-based breast reconstruction between April 2014 and Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
4
10
0
Order By: Relevance
“…Age showed a strong correlation with the total drainage volume in the univariate analysis (P = 0.011). A previous study from our institution reported the same result; older patients had a larger drainage volume 10 . The specimen weight also demonstrated a significant correlation with the total drainage volume.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Age showed a strong correlation with the total drainage volume in the univariate analysis (P = 0.011). A previous study from our institution reported the same result; older patients had a larger drainage volume 10 . The specimen weight also demonstrated a significant correlation with the total drainage volume.…”
Section: Discussionsupporting
confidence: 81%
“…The aforementioned studies excluded patients who underwent reconstructive surgery. In fact, previous studies have already shown that the type or size of tissue expander used can affect the amount of drainage volume postoperatively 8 9 10 , which provides context for the finding that the total drainage volume in our study was larger than all volumes reported in previous studies. Another aspect of how our study differed from other previous reports was in its patient selection; most studies have included all patients who underwent mastectomy, regardless of the type of breast reconstruction that followed.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, we found that volume of tissue expansion was not significantly associated with time until drain removal, which differs from the literature in that Lim et al found a strong correlation between tissue expander volume and duration of drain placement. 19 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that volume of tissue expansion was not significantly associated with time until drain removal, which differs from the literature in that Lim et al found a strong correlation between tissue expander volume and duration of drain placement. 19 There is no universal set of rules to aid surgeons' decisions on whether to pursue pre-pectoral versus dual plane reconstruction. 4 Given that no consensus exists in the literature, the surgeons in this study similarly did not follow an algorithm for determining surgical course but rather determined course based on shared decision-making with the patient.…”
Section: Prs Global Open • 2022mentioning
confidence: 99%
“…Factors influencing the time until removal of breast drains have been described in implant-based reconstruction, which remains the most frequently utilized breast reconstruction modality. [4][5][6][7] However, no similar study to date has been performed for autologous reconstruction. The timeliness of this study is compounded by recent interest in utilizing progressive barbed tension sutures for a drain free donor site closure.…”
mentioning
confidence: 99%